2000
DOI: 10.1016/s1047-9651(18)30116-5
|View full text |Cite
|
Sign up to set email alerts
|

Orthotic Management of the Neuropathic Limb

Abstract: New techniques of evaluation, risk identification, wound product application, and infection control allow limb preservation to be an extremely viable option for the neuropathic and diabetic population. The orthotist specializing in wound care brings off-loading techniques to the clinical setting to allow immediate reduction of pressure to the wound site. By reducing external forces, the ulceration responds to wound care products efficiently, and closure times decrease with optimal outcomes. Following closure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…95 The recommendation to perform barefoot plantar pressure measurement on all patients with loss of protective sensation must be tempered somewhat by the fact that there has been no prospective study showing better patient outcomes due to plantar pressure testing. Recent surveys of approaches to unloading have been given by Lavery and Murdoch, 360 van Schie, 361 van Deursen, 362 Cavanagh and colleagues, 4,73,363 Elftman, 364 and McGuire. 365,366 The need for better evidence in this area was highlighted in a Cochrane review by Spencer, 367 who found limited evidence for a variety of pressurerelieving interventions intended for the prevention and treatment of diabetic foot ulcers.…”
Section: Plantar Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…95 The recommendation to perform barefoot plantar pressure measurement on all patients with loss of protective sensation must be tempered somewhat by the fact that there has been no prospective study showing better patient outcomes due to plantar pressure testing. Recent surveys of approaches to unloading have been given by Lavery and Murdoch, 360 van Schie, 361 van Deursen, 362 Cavanagh and colleagues, 4,73,363 Elftman, 364 and McGuire. 365,366 The need for better evidence in this area was highlighted in a Cochrane review by Spencer, 367 who found limited evidence for a variety of pressurerelieving interventions intended for the prevention and treatment of diabetic foot ulcers.…”
Section: Plantar Pressurementioning
confidence: 99%
“…402 Vileikyte and her colleagues [403][404][405] stress the need for the patient to understand the disease process that is causing loss of sensation in order to maximize their compliance with advice regarding prevention. Elftman 364 has also remarked that patients are often "unaware of the neuropathic pathway until it causes a complication," and this should not be the case.…”
Section: Adherence and Educationmentioning
confidence: 99%